Frequency of Short Inter-pregnancy Interval in Neonatal Morbidities - Madiha Jameel, Sabika Iftikhar, Sadia, Sumbal Abbas, Fozia Saeed Rasul, Sumera Abdul Karim, Maha Anwar, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The risk of unfavorable perinatal outcomes in the following pregnancy may increase if there has been a short time between the last live birth and the beginning of the current pregnancy. This elevated risk may be brought on by inadequate nutritional replenishment after the delivery of a live newborn, increased cervical insufficiency, or vertical infection transmission after a brief interpregnancy intervals. Aim: To determine frequency of short interpregnancy interval in neonatal morbidities. Study design: The cross-sectional study. Methodology: The Ittefaq hospital's Neonatal ICU served as the study's location. Total 270 neonates, both sexes, 0 to 28 days old, with gestational ages between 37 and 42 weeks (based on a date scan) and birth weights between 2500 and 4000 g were included. Mothers or other witnesses of the included notates were questioned on the time between this pregnancy and the one before it. The term "short interpregnancy interval" (IPI) was used when the time between two successive pregnancies was less than 12 months. Data was analyzed in SPSS 25V. Results: Neonates ranged in age from 13.88 to 7.66 days. Neonatal mortality was 119(44.07%) male and 151(55.93%) female. It took 39.19 weeks on average, plus or minus 1.43 weeks. The average weight at birth was 2720.61 271.56 g. There were 40 neonates (14.81%) with RDS, 58 (14.81%) with NEC, 56 (20.74%) with IVH, 23(8.52%) with ROP, and 93(34.44%) with Sepsis. 200 neonates (74.07%) had a typical inter-pregnancy interval, while 70 (25.93%) had a short inter-pregnancy period. Conclusion: The study's findings indicated that 25.93% of the newborns had short inter-pregnancy intervals, which are frequently associated with neonatal morbidities. IPI is a controllable risk factor for newborn morbidity, hence it is important to urge families to choose the recommended birth spacing. Early identification of this high-risk group can help to prevent negative neonatal outcomes and identify deliveries that may require the attendance of a pediatrician. Keywords: Birth spacing, interpregnancy interval, neonatal morbidity, RDS, NEC, IVH, ROP, Sepsis